Cohort study of Western Australia computed tomography utilisation patterns and their policy implications - Gibson, David; Moorin, Rachael; Holman, C D. (BioMed Central, 2014)
Background: Computed tomography (CT) scanning is a relatively high radiation dose diagnostic imaging modality with increasing concerns about radiation exposure burden at the population level in scientific literature. This study examined the epidemiology of adult CT utilisation in Western Australia (WA) in both the public hospital and private practice settings, and the policy implications. Methods: Retrospective cohort design using aggregate adult CT data from WA public hospitals and Medical Benefits Schedule (MBS) (mid-2006 to mid-2012). CT scanning trends by sex, age, provider setting and anatomical areas were explored using crude CT scanning rates, age-standardised CT scanning rates and Poisson regression modelling. Results: From mid-2006 to mid-2012 the WA adult CT scanning rate was 129 scans per 1,000 person-years (PY). Females were consistently scanned at a higher rate than males. Patients over 65 years presented the highest scanning rates (over 300 scans per 1,000 PY). Private practice accounted for 73% of adult CT scans, comprising the majority in every anatomical area. In the private setting females predominately held higher age-standardised CT scanning rates than males. This trend reversed in the public hospital setting. Patients over 85 years in the public hospital setting were the most likely age group CT scanned in nine of ten anatomical areas. Patients in the private practice setting aged 85+ years were relatively less prominent across every anatomical area, and the least likely age group scanned in facial bones and multiple areas CT scans.Conclusion: In comparison to the public hospital setting, the MBS subsidised private sector tended to service females and relatively younger patients with a more diverse range of anatomical areas, constituting the majority of CT scans performed in WA. Patient risk and subsequent burden is greater for females, lower ages and some anatomical areas. In the context of a national health system, Australia has various avenues to monitor radiation exposure levels, improve physician training and modify funding mechanisms to ensure individual and population medical radiation exposure is as low as reasonably achievable.